Can ‘Ardhanarishvara’ resolve the Onto-logical Dualism of Prakṛti and Puruṣa? A Study in Non-Binary Ontology and fluid identity in Indian metaphysics - Kumar, Gaurav; Chadha, Ashita (Dia-noesis: A Journal of Philosophy, 2025)
In classical Indian metaphysics, particularly in the Samkhya tradition, the ontological bifurcation of Prakṛti and Puruṣa is very prevalent. This bifurcation, though crucial to Indian ontology and soteriology to explain existential queries, gives rise to persisting philosophical questions regarding the nature of the interrelation of the two. The relation between the two seems intertwined and distinct at the same time. In this context, this paper examines whether the concept of ‘Ardhanarishvara’ can be an ontological solution to this dualism, i.e., ‘Can Ardhanarishvara resolve the Ontological Dualism of Prakṛti and Puruṣa?’ ‘Ardhanarishvara’ -the composite deity uniting both Shiva and Shakti-defies the austere bifurcation of material and conscious aspects by illustrating the coexistence of opposites. Rather than seeing this figure as a mere piece of theological iconography, the question turns to Ardhanarishvara as an embodiment of symbolic metaphysics. This paper is intended to provide ‘Ardhanarishvara’ as new windows to a non-binary ontology and fluid identity of understanding that remaps identity, embodiment, consciousness, and salvation.